Identifikasi Perubahan Sifat Fisik Jambu Biji Merah (Psidium guajava L.) Selama Masa Penyimpanan pada Pendingin Evaporatif Termodifikasi - Ritonga, Abdul Mukhlis; Furqon, Furqon; Ifadah, Razifah Nur (Universitas Bangka Belitung, 2020)
Guava (Psidium guajava L.) is one of the horticultural products that could live in tropical areas and has a high economic value. Tropical fruit used to be damaged quickly remaining due to the temperature and humidity condition. Postharvest treatment is required to extend the shelf life of products and to maintain the quality of products such as evaporative coolers for storage. This research aims to: 1). Calculating the rate of decrease for red guava fruit quality during storage in an evaporative cooler and room temperature. 2). Analyze transformation in the physical properties of red guava fruit during storage in an evaporative cooler and room temperature. Variables measured are the effectiveness of cooling, temperature, relative humidity, moisture content, weight loss, hardness, brix levels, and colors. The method of this study was experimental with the object of research is guava, which has a diameter of 7-8 cm horizontal and vertical length of 6-8 cm. Guava fruits that used were obtained from guava plantation in Kampung Penyisihan, Ketenger Village. Data analysis in this study using the equations of kinetical reaction. The results showed that the treatment of evaporative cooling storage can maintain the quality of weight loss, color (Lab), and violent guava. While the temperature treatment room can maintain the quality of the water content, brix levels guava during storage.